Maximum power extraction of tidal streams - Maswood, Ali I. (2013)
This paper proposes a variable speed control scheme for a tidal in-stream power generation system. The generator used in the study is a Squirrel Cage Induction Generator (SCIG) deliberately selected due to its robustness to boisterous conditions and ease of maintenance which makes it suitable for undersea application. An in indirect vector control mode, where the d-axis stator current controls the excitation level and the q-axis stator current controls the generator torque, is utilized. In addition to the conventional dq controller the use of a second controller which dictates the machine electrical torque is proposed. Simulation results are shown to verify the validity of the proposed scheme.